Transcriptomic analysis reveals candidate molecular pathways involved in pea (Pisum sativum L.) resistance to pea aphid (Acyrthosiphon pisum Harris) biotypes - Rémi Ollivier; Stéphanie Robin; Marc Galland; Po-Yuan Shih; Stéphanie Morlière; Maria K. Paulmann; Jonathan Gershenzon; Grit Kunert; Marie-Laure Pilet-Nayel; Jean-Christophe Simon; Akiko Sugio (BMC Genomics)
Abstract Pea (Pisum sativum L.) is a major legume crop frequently infested by various parasites, including the pea aphid (Acyrthosiphon pisum Harris), which takes nutrients from its host and transmits phytopathogenic viruses. This aphid species comprises several biotypes, each one capable of feeding and reproducing on a limited range of specific legume species. However, little is known about the transcriptional response of the plants to different aphid biotypes. To investigate pea defense mechanisms against the pea-adapted and pea non-adapted A. pisum biotypes, we analyzed the transcriptional responses by mRNA sequencing of six pea genotypes with contrasting resistance levels and different haplotypes at the ApRVII locus. This locus confers partial resistance to the pea-adapted and non-adapted A. pisum biotypes. Transcriptomic analyses of pea genotypes with and without aphid infestation revealed 9,217 differentially expressed genes in pea genotypes infested with the pea-adapted aphids, while fewer genes, 1,561 genes total, were expressed in response to the pea non-adapted aphids. Both aphid biotypes activated immune responses and the biosynthesis of secondary metabolites, including flavonoids. However, the pea-adapted biotype appeared to suppress multiple pathways associated with photosynthesis, cell wall biosynthesis, fatty acid metabolism, and other growth-related processes. Candidate genes potentially involved in aphid resistance were identified both within and outside of the ApRVII locus. These findings provide insights into pea resistance mechanisms against both pea-adapted and pea non-adapted A. pisum biotypes, as well as the ability of the adapted biotype to modulate pea defenses leading to host susceptibility, and pave the way for follow-up studies, including metabolomic analyses.